A Controversial Study on The Existence of Nusatembini Kingdom in Cilacap City - Darwanto, Agus; Syalwa, Mouzya; Pratama, Darma Putra (Siginjai: Jurnal Sejarah, 2025)
The Nusatembini Kingdom on Nusakambangan Island is portrayed as a mythical kingdom because its existence is difficult to prove, but it is believed to exist, even appearing in the Babad Pasir Luhur. PT KAI once planned to launch the Nusa Tembini train route from Cilacap to Yogyakarta, but it was later canceled and renamed the Joglosemarkerto train. The Tourism Office once named a beach destination in the village of Tegalkamulyan as Nusatembini Beach, but it was soon dismantled and renamed Tegalkamulyan Beach. The existence of the Nusatembini Kingdom has raised a number of research issues, particularly regarding the historical accuracy and identity of the kingdom. This study aims to describe the factors that encourage people to believe in the existence of the Nusatembini Kingdom. Controversy has arisen due to the lack of consistent historical evidence, varying perceptions between believers and the general public, and diverse responses in the media. As a result, there are research problems surrounding a lack of understanding of the factors influencing this belief, including cultural, local historical, social dynamics, and collective community perceptions. Data collection was conducted through observation, interviews, and documentation studies. Data analysis was performed using descriptive analysis with reduction, data presentation, interpretation, triangulation, and conclusion drawing. The mythology of the Nusatembini Kingdom is closely related to the history of the Pasirluhur and Pajajaran Kingdoms. Although there is no evidence of its existence, it is recorded in the Babad Pasirluhur. There is controversy among the people of Cilacap regarding the Nusatembini Kingdom. Some believe it to be a mythical kingdom, while others say that the Nusatembini Kingdom is just a fairy tale or legend, but still others believe that the Nusatembini Kingdom did indeed exist. Prabu Pulebahas' defeat of the Pasirluhur and Pajajaran kingdoms led them to create a negative image of the Nusatembini Kingdom, spreading the story that Nusatembini was a supernatural kingdom. In fact, the Nusatembini Kingdom really did exist. Prabu Pulebahas was known as a courageous man. The negative perception of Nusatembini as a supernatural kingdom led to it being regarded only as a legend. However, the elders' rejection of the naming of Tegalkamulyan Beach as Nusatembini Beach because the location of the Nusatembini Kingdom was not there, but on the southern coast of Cilacap city or on Nusakambangan Island, is strong evidence of the existence of the Nusatembini Kingdom in the past. Thus, the people of Cilacap, especially the older generation, still believe in the existence of the Nusatembini Kingdom.